Interferometric method for image formation: the basic ideas and computer simulation - Kornienko, Yu.; Pugach, V. (Кинематика и физика небесных тел, 2005)
As it is known, the key resolution limit of an astronomical instrument is determined by diffraction of a received wave on the instrument aperture. However, by performing observations from the Earth surface in a short-wave part of the wave band, it is seldom possible to achieve this limit because of phase distortions arising by the propagation of a wave in the Earth’s atmosphere which is caused by fluctuations of the refraction index. There is a series of ideas how to form an astronomical image decreasing or excluding the influence of phase distortions during the observation. One of such methods is the interferometric imaging method. We describe this technique and present results of simulated observations of various objects and their images reconstructed for various atmospheric distortions. The advantage of a multi-beam interferometer, both by obtaining of instantaneous images and by using time accumulation is well-visible.